(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Among many aspects of reading that were under investigation rightfully and thoroughly, the effect of gender on critical thinking in general and critical thinking strategy use, in particular, seemed to be neglected. The aim of this study is to investigate the possible role of gender in the critical thinking and critical thinking strategy use of EFL learners. To do so, a qualitative case study consisting of four participants was conducted. Two of them were male and the other two were female students at the University of Mazandaran. Analysis of participants’ recorded think-aloud protocols reveals that first, gender had no role to play in the critical thinking and critical thinking strategy use; Second, both male and female participants of the study used the same variety of strategies. In this way, there was no difference in male and female strategy use and nothing particular emerged as feminine strategies.